The fashion design reference + specification book : everything fashion designers need to know every day - Calderin, Jay (Rockport Publishers, 2013)
Annotation An essential primer for students and first-stop reference for professionals, Fashion Design: An Indispensable Guidetakes the fashion designer through the entire design process, from conceiving a garment to marketing it. This valuable handbook contains the information and ideas essential to planning and executing fashion projects of every scale and distills them in an easy-to-use format that is compact enough to slip into a tote. Linking six central phases in the cycle of fashion & mdash;research, editing, design, construction, connection, and evolution & mdash;Fashion Design: An Indispensable Guidehelps designers develop effective strategies for building a cohesive collection and communicating their vision.